Entrepreneur resilience: how do entrepreneurial self-efficacy and basic psychological needs influence it? the effect of COVID-19 on Malaysia's small and medium enterprises / Dalili Izni Shafie and Salmi Mohd Isa - Shafie, Dalili Izni; Mohd Isa, Salmi (Universiti Teknologi MARA, Perlis, 2021)
The latest COVID-19 pandemic has affected industries worldwide, impacting virtually every industry and business field. Small and medium-sized businesses, in particular, have been hard hit due to a lack of funding and skills. The current study attempted to examine the impact of entrepreneurial self-efficacy and basic psychological needs on entrepreneur resilience among SMEs in Malaysia during the critical period of COVID 19. This integrated two-theory analysis article presents the findings of social cognitive theory and self-determination theory as one of the contributions to the body of knowledge in describing the relationship between a construct within the research context. Theoretical and practical implications are also discussed based on the proposed framework.